ANÁLISIS DE LA MORTALIDAD PERINATAL, HOSPITAL MIGUEL SERVET, ZARAGOZA, ESPAÑA: 2000-2009 - Esther Cruz G; María Lapresta M; Raquel Crespo E; Yasmina José G; Pilar Andrés O; Javier Tobajas H (Permanyer, 2011)
Objetivos: Evaluar la mortalidad perinatal (MP) del Hospital Miguel Servet (2000-2009). Valorar su evolución, distribución según edad gestacional y peso de los recién nacidos (RN), y las posibles causas. Método: Análisis sobre un total de 44.409 RN >500 gramos y 402 nacidos muertos ó fallecidos antes de los 28 días completos de vida. Los datos se recogieron en un formulario siguiendo las recomendaciones de la FIGO y la novena Clasificación Internacional de Enfermedades. Resultados: La MP ampliada global fue de 9,05/1000 nacidos, la mortalidad fetal de 4,91/1000 nacidos y la mortalidad neonatal 4,14/1000 nacidos vivos. La MP estándar fue de 4,73/1000 nacidos. Según la edad gestacional, un 79,6% de la MP fueron pretérminos; el 46,02% de los casos eran <1000 gramos y 59,95% <1500 gramos. Procedían de partos múltiples 92 RN (90 pretérminos); la MP de los embarazos gemelares fue 34,65/1000 nacidos. Las causas más frecuentes de MP eran: inmadurez extrema, <1000 gramos (46,02%), rotura prematura de membranas (23,13%), gestaciones múltiples (22,89%), complicaciones de placenta o cordón (21,64%), hipoxia intrauterina y asfixia al nacer (21,64%), y malformaciones congénitas y cromosomopatías (18,9%). Conclusión: La MP está gravada por la prematuridad, el bajo peso extremo y los embarazos múltiples, disminuyendo paulatinamente a expensas de la mortalidad neonatal. Objective: To evaluate Hospital Miguel Servet perinatal mortality (PM) during the years 2000-2009, valuing its evolution and distribution according to gestational age and birth weight. Maternal and fetal possible causes are analized. Methods: 44.409 newborns of >500 grams or 22 weeks gestational age, were studied. The total number of perinatal deaths was 402 containing late neonatal deaths (to 28 completed days of live). The data for each case of perinatal mortality were recorded in a form following FIGO recommendations and the 9th International Classification of Diseases. Results: Extended PM rate was 9.05/1000 newborns, fetal mortality 4.91/1000 newborns and neonatal mortality 4.14/1000 live births. Standard PM was 4.73/1000 newborns. According to gestational age, 79.60% were preterm deliveries. Considering birth weights, 46.02% were extremely low birth weight (<1000 grams), and 59.95% were <1500 grams. The number of perinatal deaths in multiple pregnancies was 92 (90 preterm deliveries). PM in twins was 34.65/1000 newborns. Main causes of death were extreme immaturity (<1000 grams) in 46.02%, premature rupture of membranes (23.13%), multiple deliveries (22.89%), complications of placenta or umbilical cord (21.64%), intrauterine hypoxia and asphyxia at birth in 21.64% of the cases, and congenital malformations and chromosomopaties (18.90%). Conclusions: PM is encumbered by prematurity, extremely low birth weight and múltiple pregnancies. Decrease of perinatal mortality had occurred mainly at the expense of neonatal mortality.